Efficient synthesis of glycerol carbonate/glycidol using 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) based ionic liquids as catalyst - Munshi, Mudassir K.; Biradar, Pradeep S.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol to glycerol carbonate has been catalyzed efficiently using basic ionic liquids as catalysts. Activity of all the ILs tested is very high and the best result (96% conversion with 82% selectivity to glycerol carbonate and 18% selectivity to glycidol) was obtained using IL1 as catalyst. The effect of catalyst loading has significant influence on the selectivity pattern. The higher activity of the ionic liquid is explained with a plausible mechanism based on the co-operative effect of both cation and anion.